Bullying na escola : abordagem e uma proposta de intervenção nos anos iniciais. - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This Critical-Reflexive Report is the outcome of a pedagogical intervention research Project on “bullying” in the school environment that has been applied on school children studying in the fifth year, elementary school year, in the Escola Municipal de Ensino Fundamental Dr. João Thiago do Patrocínio in Bagé, Rio Grande do Sul, which main objective was to make them aware of the bullying real damage, by using several playful activities, such as creating a puppet theater. Every activity was done by students and the lead teacher and one intern. The activities were created during twelve meetings, and in each one there was a proposal for a different playful activity. It was based on the violence actions inside the school involving both elementary and college students, with the possibility of leading to severe consequences for the people involved. The data have been collected from the Field journal. The research was divided into two components, being the first one interventionist, in which every meeting is described. The second one is the evaluation of this intervention, in which the instruments used to collect and analyze all the data are described. In the evaluation of the results, the improvement on the relationship among the school children that participated of the playful activities have been pointed out. Also, the school management personnel showed a great interest to link this project to the school work and used to assist the characteristics of each group. Hence, questions about the actions taken by the public authorities on trying to battle against the school bullying as well as the questions about these actions is raised, so that such violence cannot be effective spread out.
Keywords: CNPQ::CIENCIAS HUMANAS; Bullying; Intervenção; Teatro; CNPQ::CIENCIAS HUMANAS::EDUCACAO